Corrosion of metallic heritage artefacts : investigation, conservation and prediction of long term behaviour - Dillmann, P. (Philippe) (Publications (European Federation of Corrosion), 2007)
This work is broken down into four parts. The first provides an overview, the second covers the mechanisms of corrosion, measurement and prediction techniques, the third analyses archaeological finds and part four focuses on monitoring and conservation.